Structural aspekts of verbal innivations in news style - Завгородня, Анна Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
This article deals with the structural aspects of verbal innovations in the modern German language in news style. It contains short characteristics of news style, innovations (neologisms) and ways of word building. The examples were taken in period of 2014- beginning of 2015 from periodical literature from web-site «die Wortwarte». The verbal innovation were classified due to the way of word building as well as graphically showed the connection between adopted and original verb bases and affixes (prefixes, semiprefixes and suffixes).